2015
DOI: 10.1177/1687814015600666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cutting speed and feed in turning hardened stainless steel using coated carbide cutting tool under minimum quantity lubrication using castor oil

Abstract: Minimum quantity lubrication is a technique to have the advantages that cutting fluids bring yet keeping their use at minimum. For the cutting fluids, inedible vegetable oils are potential for minimum quantity lubrication machining. Castor oil was selected in this study as the cutting fluid for turning of hardened stainless steel (hardness of 47-48 HRC). The hard turning was with minimum quantity lubrication (50 mL/h flow rate and 5 bar air pressure) at various cutting speeds (100, 135, and 170 m/min) and feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…The variable levels of the machining parameters have been selected within the intervals by taking account, the recommendations of manufacturer of the cutting tool (Taegutec Ltd.) and supported by previous work of various authors for investigating surface roughness, tool wear and chip morphology (Lima et al 2005;Dogra et al 2011;Sahoo & Sahoo 2013;Shihab et al 2014;Elmunafi et al 2015;Panda et al 2016). The identified factors and their associated levels are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The variable levels of the machining parameters have been selected within the intervals by taking account, the recommendations of manufacturer of the cutting tool (Taegutec Ltd.) and supported by previous work of various authors for investigating surface roughness, tool wear and chip morphology (Lima et al 2005;Dogra et al 2011;Sahoo & Sahoo 2013;Shihab et al 2014;Elmunafi et al 2015;Panda et al 2016). The identified factors and their associated levels are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…And the quadratic mathematical models have the high determination coefficients R 2 for power consumption, surface roughness, and tool wear. And Elmunafi et al 21 also showed that the trend of influence of cutting condition including cutting speed and feed rate on surface roughness, cutting forces and tool life is similar between dry hard turning and under minimum quantity lubrication using castor oil.…”
Section: Introductionmentioning
confidence: 97%
“…Sometimes, although surface roughness is undesirable for certain manufacturing products, it is quite difficult to control and may incur higher machining costs (Singh et al, 2020). Elmunafi (2015) has reported that cutting speed is the most significant cutting parameter, followed by feed rate and depth of cut (Elmunafi et al, 2015;Tapadar et al, 2017). On the other hand, Liu (2016) has reported that feed rate is the most significant factor that affects surface roughness, followed by depth of cut and cutting velocity, for minimizing energy consumption (Liu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%